(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The essay discusses about the overall results of the Lawfulness education’s history in the Italian juvenile detention center Research carried out by CROSS, Observatory on Organized Crime of Milan State University. Through the reconstruction of the main historical phases and of the major elements of mutation, the analysis focuses on: approaches, characteristics of Italian juvenile detention center, the main successful factors and experiences of the wider framework on education of lawfulness. Keywords: lawfulness education; prison; juvenile detention center, minor; antimafia; civil history; movement.